Analysis of Epoxy Nanocomposites Characteristics by Impedance Spectroscopy. Issue 1 (23rd August 2021) - Rashmi,; Sailaja, R. R. N.; Madhu, B. M.
Abstract: The research work is carried out to analyse the electrical characteristics of glass fiber reinforced epoxy composites with the addition of multiwall carbon nanotubes and graphene nanoplatelets. The dispersion of 2wt.% multi walled carbon nanotubes(MWCNT) and 1‐3wt.% graphene nanoplatelets (GNP) into the epoxy resin is assisted with high shear mechanical mixing followed by ultrasonication. The epoxy‐filler mixture is transferred into temperature‐controlled resin bath for pultrusion process. The pultrusion process helps to resolve major issues like poor dispersion and agglomeration of nanofillers in epoxy resin. The XRD and SEM analysis indicates that fillers are dispersed homogeneously in the epoxy matrix. The electrical conductivity (σ) and impedance (Z) are studied in the frequency range (10 Hz‐8 MHz) with the variation in temperature (over 25 °C‐150 °C). It is observed that the addition of two conductive nanofillers results in a synergistic effect at the percolation threshold, and the conductivity value increases by few orders due to the formation of a number of conductive paths in the composite. The complex impedance decreases with increase in frequency for the composites except for the sample with 3wt.% GNP and 2wt.% MWCNT indicating the semiconducting behaviour. The complex impedance plot is characterized by the appearance of a single semi‐circular arc whose radii of curvature decreases with an increase in temperature, indicating the existence of electrical relaxation phenomena.